NADPH Oxidase and the Cardiovascular Toxicity Associated with Smoking - Kim, Mikyung; Han, Chang-ho; Lee, Moo-Yeol (Toxicological research (Seoul), 2014)
Smoking is one of the most serious but preventable causes of cardiovascular disease (CVD). Key aspects of pathological process associated with smoking include endothelial dysfunction, a prothrombotic state, inflammation, altered lipid metabolism, and hypoxia. Multiple molecular events are involved in smoking-induced CVD. However, the dysregulations of reactive oxygen species (ROS) generation and metabolism mainly contribute to the development of diverse CVDs, and NADPH oxidase (NOX) has been established as a source of ROS responsible for the pathogenesis of CVD. NOX activation and resultant ROS production by cigarette smoke (CS) treatment have been widely observed in isolated blood vessels and cultured vascular cells, including endothelial and smooth muscle cells. NOX-mediated oxidative stress has also been demonstrated in animal studies. Of the various NOX isoforms, NOX2 has been reported to mediate ROS generation by CS, but other isoforms were not tested thoroughly. Of the many CS constituents, nicotine, methyl vinyl ketone, and α,β-unsaturated aldehydes, such as, acrolein and crotonaldehyde, appear to be primarily responsible for NOX-mediated cytotoxicity, but additional validation will be needed. Human epidemiological studies have reported relationships between polymorphisms in the CYBA gene encoding p22phox, a catalytic subunit of NOX and susceptibility to smoking-related CVDs. In particular, G allele carriers of A640G and -930 A/G polymorphisms were found to be vulnerable to smoking-induced cardiovascular toxicity, but results for C242T studies are conflicting. On the whole, evidence implicates the etiological role of NOX in smoking-induced CVD, but the clinical relevance of NOX activation by smoking and its contribution to CVD require further validation in human studies. A detailed understanding of the role of NOX would be helpful to assess the risk of smoking to human health, to define high-risk subgroups, and to develop strategies to prevent or treat smoking-induced CVD.